A39 NON-VITAMIN K ANTAGONIST ORAL ANTICOAGULANTS AND GASTROINTESTINAL BLEEDING: A NETWORK META-ANALYSIS. (1st March 2018) - Dorreen, A; Miller, C; Martel, M; Barkun, A N
Abstract: Background: *Drs. Alastair Dorreen and Corey Miller are co-first authors Several non-vitamin K antagonist oral anticoagulants (NOACs) have been approved for clinical use. A recent meta-analysis of randomized controlled trials (RCTs) and some observational data have suggested an increased risk of gastrointestinal bleeding (GIB) with dabigatran and rivaroxaban compared to conventional anticoagulation, yet data regarding comparative risk of GIB between NOACs are limited. Aims: To conduct a network meta-analysis to assess the comparative risk of GIB between NOACs. Methods: An initial search for RCTs comparing NOACs to conventional anticoagulation therapy was performed using the EMBASE, Medline, Cochrane and ISI Web of knowledge databases through January 2017. Trials assessing NOACs for the treatment of acute coronary syndrome and other unapproved indications were excluded. The primary outcome of comparison was the risk of GIB via a network meta-analysis with random effects model using the netmeta package in R 3.2 (www.r-project.org ). Results: A total of 51 trials were included, randomizing 180, 853 patients. When comparing dabigatran vs. apixaban (OR: 1.72, 95% CI: 0.90; 3.30), dabigatran vs. edoxaban (OR: 1.32, 95% CI: 0.66; 2.64), dabigatran vs. rivaroxaban (OR: 1.11, 95% CI: 0.60; 2.04), rivaroxaban vs. apixaban (OR: 1.55, 95% CI: 0.84; 2.87), rivaroxaban vs. edoxaban (OR: 1.19, 95% CI: 0.61; 2.33) and apixaban vs. edoxaban (OR: 0.77, 95% CI: 0.38; 1.55), there was no significant difference in odds of major GIB. Secondary analysis did not reveal any difference in the odds of major GIB when comparing individual NOACs to warfarin, low-dose enoxaparin, placebo or aspirin. Conclusions: Overall, the risk of major GIB was equivalent between NOACs when compared head-to-head in a network meta-analysis. Further high-quality studies are needed to characterize GIB risk among individual NOACs. Funding Agencies: None